Hubungan Karakteristik Ibu dengan Pengetahuan tentang Penatalaksanaan Diare pada Balita - Dwi Novrianda; Fitra Yeni; Asterina (NERS Jurnal Keperawatan, 2014)
The role of mother in management of diarrhea is very important that is expected can reduce morbidity and mortality rate cause diarrhea. In this study we attempted to assess the correlation between mother’s characteristic based on age, education level, occupational status, and economic status with knowledge about management of diarrhea to children under five. It has done from March 1st - August 9th 2004 with 97respondents. The design was a cross-sectional study with simple random sampling. Data was collected by guided interview with questioner and analyzed by distribution of frequency table and tested by chi-square method. From this study, there was 55,7 % are in old group (31-45 year’s old); 45,4 % respondents had low education; 90,7 % respondents were not active; 57,7 % were poor. Generally, the knowledge of respondents about management of diarrhea to children under five 58,8 % were bad. We conclude that there was significant relation between age, education level, and economic status with knowledge about management of diarrhea to children under five. Thus, it’s need to improvement of mother’s knowledge by information to the people.